Teori Identitas Sosial dalam Konteks Media Sosial: Systematic Literature Review tentang Pembentukan In-group dan Out-group di Era Digital - Mu’adzah, Hanifah Alya (Lembaga Yasin AlSys, 2026)
This study examines the dynamics of in-group and out-group formation on social media from the perspective of Social Identity Theory, employing a systematic literature review approach. Literature searches were conducted in the Scopus, Web of Science, and Google Scholar databases for publications from 2019 to 2025. Of the 309 articles initially identified, 10 met the inclusion criteria after a screening process using the PRISMA protocol. The analysis shows that in-group formation is facilitated by platform algorithms, virtual community features, and social identification processes reinforced by online interactions, whereas out-group formation occurs through mechanisms of social comparison, stereotypes strengthened by echo chambers, and intergroup competition. In the digital era, social identity appears more flexible and dynamic than in offline contexts, with social media acting as a catalyst that accelerates processes of group categorization and polarization. These findings have important implications for understanding social polarization and online radicalization, as well as for developing digital literacy-based intervention strategies to mitigate the negative impacts of social identity dynamics in virtual spaces.